Carcinoma-rectum in an 11 years old boy - Afroza, A; Hasan, S; Rukunuzzaman, M; Hussain, SA; Amin, R (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S70-72The abstract of this article is available on the PubMed website